Effects of Time since Diagnosis on the Association between Parent and Child Distress in Families with Pediatric Cancer - Okado, Yuko (Child Health Care, 2015)
Although parental distress and child distress have been linked in families of children with cancer, how these associations change over time is unknown. The present study examined how the amount of time elapsed since the child’s diagnosis moderates the associations between self-reported parent and child symptoms of depression, anxiety, and post-traumatic stress in 255 parent-child dyads. Time since diagnosis moderated the associations between parental symptoms and child-reported anxiety and post-traumatic stress. Dyads farther out from diagnosis exhibited stronger associations between parental and child symptoms. Findings suggest the importance of monitoring the psychological adjustment of parents and children over time.